2018
DOI: 10.3389/fpsyg.2018.02325
|View full text |Cite
|
Sign up to set email alerts
|

Proprioceptive Indicators of Personality and Individual Differences in Behavior in Children With ADHD

Abstract: Researchers have suggested that the link between personality traits and Attention-Deficit/Hyperactivity Disorder (ADHD) could be a crucial factor in understanding the disorder’s diatheses. The aim of our study was to contribute to research on personality differences (based on fine motor precision – a novel approach) in children with and without ADHD symptoms. The Children Sustained Attention Task (CSAT) and Proprioceptive Diagnostics of Temperament and Character (DP-TC) were administered to children with an AD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Revising further recent research, some findings are unclear or even contradictory in relation to sex differences and motor precision, velocity, and asymmetry and these parameters seem to be age-related. In both, primary school (8)(9)(10)(11)(12) and high school students (15)(16)(17)(18), girls showed prevalence in handwriting short copy tasks vs. boys, while in another longitudinal study (7)(8)(9)(10)(11), copywriting tasks did not reveal any significant sex differences [14]. A male advantage in motor learning rather than in motor performance was found in male adolescents compared to female adolescents [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Revising further recent research, some findings are unclear or even contradictory in relation to sex differences and motor precision, velocity, and asymmetry and these parameters seem to be age-related. In both, primary school (8)(9)(10)(11)(12) and high school students (15)(16)(17)(18), girls showed prevalence in handwriting short copy tasks vs. boys, while in another longitudinal study (7)(8)(9)(10)(11), copywriting tasks did not reveal any significant sex differences [14]. A male advantage in motor learning rather than in motor performance was found in male adolescents compared to female adolescents [14].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the complexity of comparing the results obtained by different studies consists not only of the important factor of age, as shown by the above literature review, but also of other aspects, such as the type of tasks and sensory conditions used in those tests. Sometimes, other factors can also influence fine motor performance in men and women, such as socio-economical status [15], individual [16], and cultural differences [10] among others; these factors should be considered in interpretations whenever possible. In addition, the important role of proprioception for motor tasks and perception of space was observed in previous studies, together with the crucial role of the integrative system vision with proprioception [17].…”
Section: Introductionmentioning
confidence: 99%
“…As other studies have shown, proprioceptive accuracy of fine motor movements is agedependent, deteriorating during adolescence (up to 18 years old) and gradually decreasing after 50 years old due to aging processes [11]. Individual differences in fine motor accuracy are important indicators of health and may be associated with various conditions such as Parkinson's disease [12], adaptation to stress in sportsmen [13], adaptation to stress in cancer patients [1], and children with ADHD [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The complexity of comparing the results obtained by different studies consists not only of the important factor of age, as shown by the above literature review, but also of other aspects, such as the type of tasks and sensory conditions used in tests. Sometimes, other factors can influence also on fine motor performance in men and women, such as socio-economical status [3], individual [4] and cultural differences [5] among others; and should be considered in interpretations if it is possible. The important role of proprioception for motor tasks and perception of space was Preprints (www.preprints.org) | NOT PEER-REVIEWED | Posted: 15 November 2019 doi:10.20944/preprints201911.0168.v1…”
Section: Introductionmentioning
confidence: 99%